Physical Activity Among Children With Congenital Heart Defects in Germany: A Nationwide Survey - Siaplaouras, Jannos; Niessner, Claudia; Helm, Paul C.; Jahn, Annika; Flemming, Markus; Urschitz, Michael S.; Sticker, Elisabeth; Abdul-Khaliq, Hashim; Bauer, Ulrike M.; Apitz, Christian (Frontiers in Pediatrics, 2020)
Objective: In children with congenital heart defects (CHD), a sedentary lifestyle should be avoided and usually WHO recommendations on physical activity (PA) are supposed to be followed. In order to obtain representative data of the actual amount of PA (and potential influencing factors) in children with CHD we performed a nationwide online survey. Methods: All patients aged 6 to 17 years registered in the German National Register for CHD were contacted by email and asked to participate in the survey using the comprehensive questionnaire of the ”Motorik-Modul“ from the German Health Interview and Examination Survey for Children and Adolescents (KiGGS), thus allowing the comparison with a representative age-matched subset of 3.385 participants of the KiGGS study. The questionnaire for CHD-patients was amended by specific questions regarding medical care, sports recommendations and PA restrictions. Results: Complete datasets of 1.198 patients (mean age of 11.6 ± 3.1 years) were available for evaluation. Compared to the reference group, CHD patients significantly less frequently reached the WHO recommended level of 60 minutes of daily PA (8.8% versus 12%; p < .001). Enjoyment in sports was almost equally distributed across CHD and reference groups, and strongly correlated with the level of PA (r=0.41; p < .001). Remarkably, 49.2% of children with complex CHD, 31.7% with moderate, and even 13.1% with simple CHD were advised by their physician to restrict PA. Conclusions: According to this nationwide survey, PA is markedly reduced in children with CHD. An important reason for this might be an unexpected high rate of physician-recommended restrictions on levels of PA.